2021
DOI: 10.1007/s10344-021-01467-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential importance of urban areas for water voles: Arvicola amphibius

Abstract: Cities are not often considered priority areas for threatened mammals; however, recent research suggests that urban areas may be important for water vole (Arvicola amphibius) conservation. To establish the potential importance of cities in supporting water vole populations we used National Biodiversity Network (NBN) Atlas data to examine the occurrence of water voles within the United Kingdom (UK). Water voles were recorded in 28 out of 64 official UK cities in the last decade (2010)(2011)(2012)(2013)(2014)(20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…However, herons typically wash mammalian prey before ingestion, so it is possible that some floating propagules may attach to fur then. The widespread occurrence of water voles in U.K. samples is striking given their threatened status (Leivesley et al., 2021; Mathews et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, herons typically wash mammalian prey before ingestion, so it is possible that some floating propagules may attach to fur then. The widespread occurrence of water voles in U.K. samples is striking given their threatened status (Leivesley et al., 2021; Mathews et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has more than 200 members and allows recording, sharing, displaying, and downloading species records. Records of species sightings are uploaded to the Atlas by registered organisations where datasets are collected by citizen science campaigns [ 26 ]. NBN datasets have previously proved useful in studying distribution patterns of UK species [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Britain's road verges provide habitats to mice and voles (Bellamy et al 2000), and residential gardens are utilised by bats, foxes, squirrels, hedgehogs, mice and voles (Baker and Harris 2007). Rivers and streams within parks, sports grounds, and urban reserves are important habitats for water voles in urban areas in the UK (Leivesley et al 2021). Additionally, research on West European hedgehogs has shown that their numbers have declined markedly in the UK, but that they are still commonly present in areas of human habitation (Williams et al 2018;Gazzard et al 2021).…”
Section: Introductionmentioning
confidence: 99%